2020
DOI: 10.3390/s20185326
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Estimation of Machining Parameters during End-Milling Operations Based on Acoustic Emission

Abstract: This work presents a non-invasive and low-cost alternative to traditional methods for measuring the performance of machining processes directly on existing machine tools. A prototype measuring system has been developed based on non-contact microphones, a custom designed signal conditioning board and signal processing techniques that take advantage of the underlying physics of the machining process. Experiments have been conducted to estimate the depth of cut during end-milling process by means of the measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In a previous work, a single microphone implementation was developed based on traditional signal processing and a geometric model of the process [ 14 ]. This method required a simpler setup and calculation algorithm, but the signal was highly contaminated by other sources of noise and reverberation, limiting the system’s precision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous work, a single microphone implementation was developed based on traditional signal processing and a geometric model of the process [ 14 ]. This method required a simpler setup and calculation algorithm, but the signal was highly contaminated by other sources of noise and reverberation, limiting the system’s precision.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was found that acoustic emission waves picked up by microphones have mostly low frequency components [ 14 ]. Since the highest frequency component that would be measured was 200 Hz, then, its wavelength would be about 1720 mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method has also been used to detect On Load Tap Change and amplified the received recording signal. The signal is analysed through extraction of Power Spectrum Density (PSD) using the Welch method (Welch PSD), and the detail of the energy coefficient is determined by using a Haar wavelet [74,75]. Furthermore, AE can be used to estimate cutting depth during the end-milling process by measuring the acoustic emissions generated during the drilling operation.…”
Section: Acoustic Emission Sensingmentioning
confidence: 99%
“…Numerous studies have been conducted in which AE sensing was used to monitor conditions during various machining operations, such as turning [8][9][10][11], milling [12][13][14][15], reaming [16], honing [17,18], grinding [19][20][21][22][23], or polishing [24][25][26]. Several AE sensing studies have also been reported for drilling [27][28][29]; for example, Gómez and Ferrari described correlations between various AE parameters and thrust force and tool wear [30,31], whereas Patra reported the usefulness of an artificial-neural-network model based on wavelet-packet features for evaluating flank wear [32].…”
Section: Introductionmentioning
confidence: 99%